CSF Obstruction and Malabsorption in Congenital Hydrocephalus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The relative contribution of CSF malabsorption and obstruction in three different etiological groups of neonatal high-pressure hydrocephalus (HC) was assessed in a study at University of Bonn, Germany, and University of Groningen, The Netherlands.